2021
DOI: 10.1111/cge.14042
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial interventions and needs among individuals and families with Li‐Fraumeni syndrome: A scoping review

Abstract: Li-Fraumeni syndrome (LFS), a rare cancer predisposition syndrome caused by germline mutations in the TP53 gene, is associated with significant lifetime risk of developing cancer and warrants extensive and long-term surveillance. There are psychosocial impacts on individuals and families living with this condition, from the initial diagnosis throughout multiple stages across the lifespan, but these impacts have not been systematically reviewed and organized. The objective of this scoping review was to synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 71 publications
(159 reference statements)
0
5
0
Order By: Relevance
“…Although decision-making is usually conducted by their guardians, it is essential that children are included in the process, after consideration of their capacity and conditions [30][31][32]36]. Providing a space where children, especially adolescents, and parents can both express their thoughts and receive advice in the absence of their parents/children is helpful.…”
Section: Key Pointsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although decision-making is usually conducted by their guardians, it is essential that children are included in the process, after consideration of their capacity and conditions [30][31][32]36]. Providing a space where children, especially adolescents, and parents can both express their thoughts and receive advice in the absence of their parents/children is helpful.…”
Section: Key Pointsmentioning
confidence: 99%
“…Surveillance can influence individuals' lives in various aspects. Frequent medical visits and travel distance can create logistical difficulties [36,53]. The cost of surveillance varies according to the healthcare system.…”
Section: Surveillancementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is not unusual that these families have multiple affected family members simultaneously. A recently published review on several psychosocial aspects of being a TP53 carrier in surveillance identified need for psychosocial support for these families 10 . Because of the high cancer risks, the European guidelines from 2020 11 recommend surveillance with whole‐body MRI (WB‐MRI) to carriers of all ages, although in many countries, including Sweden, this has not yet been implemented in routine care.…”
Section: Introductionmentioning
confidence: 99%
“…A recently published review on several psychosocial aspects of being a TP53 carrier in surveillance identified need for psychosocial support for these families. 10 Because of the high cancer risks, the European guidelines from 2020 11 recommend surveillance with wholebody MRI (WB-MRI) to carriers of all ages, although in many countries, including Sweden, this has not yet been implemented in routine care. In the Swedish TP53 Study (SWEP53), adult carriers are offered routine surveillance with WB-MRI including MRI of the breasts and brain.…”
Section: Introductionmentioning
confidence: 99%